Physostigmine: A Plant Alkaloid Isolated from Physostigma venenosum: A Review on Pharmacokinetics, Pharmacological and Toxicological Activities - Batiha, Gaber El-Saber; Alkazmi, Luay M.; Nadwa, Eman H.; Rashwan, Eman K.; Beshbishy, Amany Magdy; Shaheen, Hazem; Wasef, Lamiaa (Journal of Drug Delivery and Therapeutics, 2020)
Medicinal plants have been documented as an important source for discovering new pharmaceutical molecules that have been used to treat serious diseases. Strikingly, previous reports stated that natural products and their derived compounds exhibit lesser side effects and improved efficacy than other synthetic counterparts. Physostigmine, a parasympathomimetic plant alkaloid isolated from the West African perennial shrub Physostigma venenosum, it shows a narrow therapeutic index and a short life span, despite its ability to penetrate the blood-brain barrier (BBB). It is a widely known reversible butyrylcholinesterase (BuChE) and acetylcholinesterase (AChE) inhibitor and has been documented to treat various ailments such as Alzheimer’s disease. Pharmacologically, physostigmine was first reported as an antidote for atropine scopolamine and belladonna alkaloids toxicity. Recently, it has been documented as a therapy for treating several ailments including glaucoma, myasthenia gravis and the intoxication caused by tricyclic antidepressant overdoses, anti-histamines, antipsychotics, and benzodiazepines. Physostigmine has been reported to be absorbed from the gastrointestinal tract and showed short half-life, as, after the oral administration of 2 mg of physostigmine salicylate, the peak plasma concentration reached to 30 minutes. This review examines the biological activities, pharmacokinetics, and toxicity of physostigmine extracted from P. venenosum. Keywords: Physostigma venenosum, Physostigmine, pharmacological activities, acetylcholinesterase and butyrylcholinesterase inhibitor.